The Bipolaron Model In Transport Properties Of Yba2cu3oy Superconductor Prepared By Adding Pr2co7 Magnetic Nanoparticles - Mani Kongnine, D.; Hamrita, A.; Napo, K. (University of Eloued جامعة الوادي, 2017)
Samples with the addition of ferromagnetic nanoparticles of Pr2Co7 on YBa2Cu3Oy (YBCO) polycrystalline superconductor were prepared by the standard solid state reaction method. The analysis of x-ray diffraction patterns by Rietveld refinement indicates orthorhombique to tetragonal phase transformation and oxygen rate reduction from x=0.3% of Pr2Co7 content. Resistivity at room temperature increases as Pr2Co7 content increases. The normal state resistivity versus temperature was analyzed properly by the bipolaron model. It suggested the increase of mobile charge localization with Pr2Co7 content.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 02
Keywords: Pr2Co7 ferromagnetic nanoparticles, high temperature superconductor, bipolaron model, localization of mobile charge.